A Neurosurgeon's Guide to Cognitive Dysfunction in Adult Glioma. Issue 1 (8th December 2020) - Morshed, Ramin A; Young, Jacob S; Kroliczek, Arlena A; Berger, Mitchel S; Brang, David; Hervey-Jumper, Shawn L
Abstract: Cognitive decline is common among patients with low- and high-grade glioma and can significantly impact quality of life. Although cognitive outcomes have been studied after therapeutic interventions such as surgery and radiation, it is important to understand the impact of the disease process itself prior to any interventions. Neurocognitive domains of interest in this disease context include intellectual function and premorbid ability, executive function, learning and memory, attention, language function, processing speed, visuospatial function, motor function, and emotional function. Here, we review oncologic factors associated with more neurocognitive impairment, key neurocognitive tasks relevant to glioma patient assessment, as well as the relevance of the human neural connectome in understanding cognitive dysfunction in glioma patients. A contextual understanding of glioma-functional network disruption and its impact on cognition is critical in the surgical management of eloquent area tumors.